Three-level containment model of hospitalized adolescents with borderline pathology: a holistic therapeutic perspective - Robin, Marion; Bellone, Laura; Belbèze, Jean; Kazemian, Koucha; Radjack, Rahmeth; Corcos, Maurice (Frontiers in Psychiatry, 2023)
Borderline personality disorders represent 50% of adolescent hospitalisation cases in psychiatry. The severity of the symptoms and their psychopathological complexity indicate that the models of understanding cannot afford to be exclusive. A holistic approach enables one to take the patient's environment into account as well as their place in this environment and their position in their life history. This article develops a model based on the notion of therapeutic containing on three levels. Global containing describes the state of mind and organisation of the institution that receives the patient, which is itself included in society at a given time. Local containing is based on the understanding and therapeutic work of the subject's relationships in their immediate environment. Finally, individual containing defines the constitution of the patient's independent processes during care. These three levels are articulated during the hospital treatment of these disorders in a work of trans-theoretical integration.